(untitled) - Duong, Thu Huong (New York, 1996)
Novel Without a Name will shatter every preconception Americans have about what happened in the jungles of Vietnam. With Duong Thu Huong, whose Paradise of the Blind was published to high critical acclaim in 1993, Vietnam has found a voice both lyrical and stark, powerful enough to capture the conflict that left millions dead and spiritually destroyed her generation.
Keywords: Vietnamese fiction,Tiểu thuyết Việt Nam; 20th century,Thế kỹ 20